Molecular nutrition and genomics : nutrition and the ascent of humankind - Lucock, Mark (John Wiley & Sons, 2007)
This fascinating book draws it subject matter from a range of relevant disciplines that extend from molecular nutrition, nutritional sciences, and nutrition dietetics through to genetics, genomics, and anthropology. It presents a vital portrait of the absolutely fundamental role that nutrition has played and continues to play in shaping who and what human beings are, as well as where they evolved from, and where they may be heading as a species. Molecular Nutrition: Nutrition and the Evolution of Humankind:* Blends coverage of the molecular mechanisms that underpin nutrient-gene interactions with evolutionary theory* Takes a molecular biological approach to problem solving, and moves nutrition away from its dietetic and anthropological origins to the front lines of genomic research* Covers key concepts in molecular biology; the -omics revolution and bioinformatics; recent human evolution; molecular mechanisms of gene-nutrient interactions; the importance of nutrients and genomics in disease; the evolution of micronutrient metabolism, protein structure, and human disease; nutrients and the human lifecycle; contemporary dietary patterns; leading-edge laboratory tools in nutrigenomics and human evolutionary studiesWritten by an internationally recognised expert in the field, Molecular Nutrition: Nutrition and the Evolution of Humankind is an invaluable text and reference book for a wide range of teachers, students, and researchers.